2020
DOI: 10.1016/j.psj.2020.03.033
|View full text |Cite
|
Sign up to set email alerts
|

The adaptability of Hy-Line Brown laying hens to low-phosphorus diets supplemented with phytase

Abstract: Body phosphorus homeostasis network allows laying hens to adapt to wide range of changes in dietary phosphorus levels. Phytase hydrolyzes phytate rendering phosphorus and reduces the laying hens' requirements for inorganic phosphate rock. Here, we demonstrate that there is no need to keep large safety margins in dietary phosphorus when hens are fed with phytase. Hy-Line Brown laying hens (n = 504) were randomly assigned to 7 treatments (6 replicates of 12 birds). A corn-soybean meal–based diet, with no inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
(43 reference statements)
0
11
1
1
Order By: Relevance
“…For instance, some studies have observed an increase in P digestibility in hens fed with P-deficient diets, both at fecal and ileal level [ 27 ], reducing P excreta [ 28 ]. In fact, Ren et al [ 29 ] reported that when dietary inorganic P was overdosed, it was mainly excreted by the laying hens. Regarding Ca, although some studies observed a decrease in Ca digestibility when dietary inorganic P was overdosed [ 29 ], others have observed the opposite behavior, decreasing Ca digestibility in Ca-deficient diets [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, some studies have observed an increase in P digestibility in hens fed with P-deficient diets, both at fecal and ileal level [ 27 ], reducing P excreta [ 28 ]. In fact, Ren et al [ 29 ] reported that when dietary inorganic P was overdosed, it was mainly excreted by the laying hens. Regarding Ca, although some studies observed a decrease in Ca digestibility when dietary inorganic P was overdosed [ 29 ], others have observed the opposite behavior, decreasing Ca digestibility in Ca-deficient diets [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Ren et al [ 29 ] reported that when dietary inorganic P was overdosed, it was mainly excreted by the laying hens. Regarding Ca, although some studies observed a decrease in Ca digestibility when dietary inorganic P was overdosed [ 29 ], others have observed the opposite behavior, decreasing Ca digestibility in Ca-deficient diets [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations